Tribological performance of titanium alloy Ti–6Al–4V via CVD-diamond coatings - Din, S.H.; Shah, M.A.; Sheikh, N.A. (Сверхтвердые материалы, 2018)
In the present study, HFCVD nanocrystalline, microcrystalline and boron-doped nanocrystalline diamond coatings have been deposited on titanium alloy. The effect of boron doping on coefficient of friction and residual stresses of diamond coatings have been studied. Досліджено нанокристалічні, мікрокристалічні і леговані бором нанокристалічні алмазні покриття, нанесені на титановий сплав. Вивчено вплив легування бором на коефіцієнт тертя і залишкові напруги алмазних покриттів. Исследованы нанокристаллические, микрокристаллические и легированные бором нанокристаллические алмазные покрытия, нанесенные на титановый сплав. Изучено влияние легирования бором на коэффициент трения и остаточные напряжения алмазных покрытий.